Prevention and management of occupational violence and aggression in healthcare: A scoping review. Issue 6 (December 2018) - Morphet, J.; Griffiths, D.; Beattie, J.; Velasquez Reyes, D.; Innes, K.
Abstract: Background: Workplace violence is prevalent in healthcare, and significant resources have been invested in its prevention and management. Internationally, guidance materials developed by government and non-government bodies advise on the management of workplace violence, yet a dearth of research to support these interventions exists. Aim: To examine the evidence relating to the effectiveness of interventions to prevent and manage workplace violence perpetrated by consumers in healthcare. Methods: A scoping review method was used. Scopus, OVID Medline, PubMed, CINAHL Plus, ProQuest Central, and Google Scholar were searched and 2276 results were retrieved. Following screening by title and abstract, 126 papers were retrieved for full-text review, and 20 papers were included in the final study. Meta-analysis could not be undertaken due to variation in study design. Therefore data are reported using a narrative framework. Findings: Interventions which reduced workplace violence included consumer risk assessment, staff education, and aggression management teams. Increasing visibility, in conjunction with other measures, also reduced the incidence of workplace violence. Post-incident support, in the form of group debriefing, increased the incidence of violent incidents, but this may be due to increased awareness of the importance of reporting. No evidence was found in relation to the use of duress alarms, incident reporting, or zero tolerance policies. Discussion: There is clear evidence underpinning some interventions used to manage workplace violence in healthcare, further research is needed to demonstrate the effect of widely used interventions such as zero tolerance policies, incident reporting and duress alarms.